The Importance of stakeholder involvement in strategic development of destination management - Žibert, Maja (Academica turistica, 2017)
The aim of this paper is to explain further the importance of stakeholder involvement in strategic development of destination management with the purpose of getting a deeper understanding of what different stakeholders perceive as more or less important when it comes to destinationmanagement. Key concepts of strategic and destinationmanagement are explained in the theoretical part. Based on this, we have posed ourselves the main research question: What are the desires of different stakeholders in the development of the destination in the light of strategic management? Explanations and viewpoints of other authors were summarized, and attempts were made to derive new viewpoints based on our research questions. Results confirmthe findings that the life of the local population should be included and engaged actively in the development, when developing the destination and identifying the potentials. Each group of stakeholders plays a special role in the development of the destination. This paper offers an overview of the analysis challenges and trends in the development of a small tourist destination. The most reasonable and appropriate for small destinations is to undertake the management of "bottom-up" and to consider a common brand, whichwill provide recognition of the place and its key tourism products.
Keywords: Dolenjska; lokalne skupnosti; Lower Carniola; management; poslovna strategija; tourism; turistične destinacije; turizem